Solar-driven plasmonic heterostructure Ti/TiO2−x with gradient doping for sustainable plasmon-enhanced catalysis. Issue 15 (1st April 2020) - Cheng, Chaoqun; Akram, Muhammad Nadeem; Nilsen, Ola; Pryds, Nini; Wang, Kaiying
Abstract : Plasmonic heterostructure Ti/TiO2− x with gradient doping exhibits strong surface plasmon resonances in the visible light spectrum for sustainable plasmon-enhanced catalysis. Abstract : Plasmon-enhanced harvesting of photons has contributed to the photochemical conversion and storage of solar energy. However, high dependence on noble metals and weak coupling in heterostructures constrain the progress towards sustainable plasmonic enhancement. Here earth-abundant Ti is studied to achieve the plasmonic enhancement of catalytic activity in a solar-driven heterostructure Ti/TiO2− x . The heterostructure was fabricated by engineering an intense coupling of a surface-etched Ti metal and a gradient-based TiO2− x dielectric via diffusion doping. Ti/TiO2− x exhibits a highly resonant light absorption band associated with surface plasmon resonances that exhibit strong near-field enhancement (NFE) and hot electron injection effects. In a photoelectrochemical system, intense interaction of the resonant plasmons with a vicinal TiO2− x dielectric accelerates the transfer of solar energy to charge carriers for plasmon-enhanced water splitting reactions. Moreover, the plasmonic Ti/TiO2− x structure presents sustained enhanced redox activities over 100 h. The intense coupling by gradient doping offers an effective approach to enable the plasmon resonances of Ti excited by visible light. The Ti-based plasmonic heterostructure potentially opens an alternative avenue towards sustainable plasmon-enhanced catalysis.